2014
DOI: 10.1007/s10661-014-3744-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water salinity on corrosion risk—the case of the southern Baltic Sea coast

Abstract: Water corrosivity in Gdansk Bay, Poland, the southern part of the Baltic Sea, was investigated. The analysed region is heavily industrialized, and the coastline is very diverse. Twenty-seven test points along the coastline were selected. Water parameters such as salinity, total dissolved solids content, resistivity, conductivity, oxygenation, pH and corrosion rate were determined. The results of the investigation are presented. Water samples were collected, and structural steel specimens were exposed in the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
3
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 42 publications
0
42
3
5
Order By: Relevance
“…The similar magnitude of conductivity in the different seawater sites points to a similar concentration of dissolved ions or total dissolved various salts. Corrosion rates tend to increase when water conductivity increases [14]. However, the present results show that the corrosion rate of the steel in all test solutions tended to increase up to 1 month of exposure but there was no change in conductivity level in the solutions.…”
Section: Figurecontrasting
confidence: 66%
See 2 more Smart Citations
“…The similar magnitude of conductivity in the different seawater sites points to a similar concentration of dissolved ions or total dissolved various salts. Corrosion rates tend to increase when water conductivity increases [14]. However, the present results show that the corrosion rate of the steel in all test solutions tended to increase up to 1 month of exposure but there was no change in conductivity level in the solutions.…”
Section: Figurecontrasting
confidence: 66%
“…The breakage of the passive film is an active site for anodic reactions. ] [14]. It should be noted that Cl -ions in seawater are correlated mainly to the NaCl, MgCl 2 and KCl content [15].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Cl´ions act as a catalyst and phase distributor for iron corrosion (rust formation) [63][64][65][66][67][68][69]. The redox (Eh, pH) relationships for Cl, Fe and Na species (ions and precipitants) are provided in [63].…”
Section: B2 Direct Catalytic Reaction With Zvimentioning
confidence: 99%
“…Many researchers have studied the mechanism of steel corrosion in marine and offshore environments. Jyoti et al [5] summarized previous research work and reported that temperature [6], pH value [7], salinity [8], dissolved oxygen [9], and water velocity [10] were the main physical factors that affected the corrosion responses of steel. Besides the investigation of corrosion factors, other studies have focused on mechanism optimization.…”
Section: Introductionmentioning
confidence: 99%